Drivers and obstacles for implementing Industry 4.0 technologies - Bingsmark, John Wilhelm Detlof (2022)
The world is in the midst of a forth industrial revolution known as Industry 4.0. New technologies based on the Internet of Things, Cyber-Physical Systems and Smart Factories are radically changing the way the world thinks about manufacturing. However, because of the novelty of these technologies, there exist no best practices for companies to follow and existing literature on the subject is limited. To complement existing literature and provide good practices for companies, this research aims to identify the main drivers and obstacles for implementing Industry 4.0 technologies. By interviewing five global manufacturing companies, we identified 12 drivers and 13 obstacles for implementing industry 4.0 technologies: Drivers for implementing Industry 4.0 technologies: Reducing costs, Improving quality, Improving operational efficiency, Increasing competitiveness, Enhancing the product, Improving working conditions, Increasing employer attractiveness, Increasing revenues and profits, Hedging against future disruption, Knowledgeable and supportive leadership, Improving time-to-market and Producing small volumes of goods. Obstacles for implementing Industry 4.0 technologies: Legacy systems, Cyber security concerns, Attracting a new skillset, Option overload, Continuous training and accompaniment of employees, Large financial investment, Legal constraints, Favouring of ongoing production over future ideas, Lack of knowledge and benefit realization, Lack of trust, Lack of standards, Lack of mature data points, Lack of technology maturity. These results adds weight to the currently sparse literature on the subject. They also give managers a better idea of why they should implement Industry 4.0 technologies and what challenges they might face while doing so.